Pemanfaatan TikTok Sebagai Sarana Strategi Komunikasi Branding Universitas Tarumanagara - Pasanea, Debora Natalia; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The increasing number of universities in Indonesia has led to higher competition between universities to attract the attention of prospective students. Therefore, it is important for a university to maintain its reputation by implementing personal branding. This research discusses on the personal branding strategy of a private university through social media. This research studied on Untar's personal branding strategy through @untarjakarta TikTok account. The methodology used in this research is qualitative methodology with data collection techniques through interviews, observation, and documentation. The theories used are public communication theory, personal branding concept, and employer branding. After conducting the research process, it can be concluded that Untar Public Relations utilizes TikTok @untarjakarta social media to build an impression or branding to the public. This strategy is done by using six personal branding concepts, namely specialization, personality, difference, appearance, unity, and constancy. In order to build an honest and credible reputation to the public, Untar Public Relations uses real and active students as talents on @untarjakarta TikTok account. Peningkatan jumlah perguruan tinggi di Indonesia, menyebabkan semakin tingginya persaingan antara perguruan tinggi untuk menarik perhatian calon mahasiswa. Sehingga penting bagi sebuah perguruan tinggi untuk mempertahankan reputasi dengan melakukan personal branding. Penelitian ini membahas bagaimana strategi personal branding perguruan tinggi swasta melalui media sosial. Peneliti mengambil studi pada strategi personal branding Untar melalui TikTok @untarjakarta. Metodologi yang digunakan peneliti adalah metodologi kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Teori-teori yang digunakan adalah teori komunikasi publik, konsep personal branding, dan employer branding. Setelah melakukan proses penelitian, dapat ditarik kesimpulan bahwa Humas Untar memanfaatkan media sosial TikTok @untarjakarta guna membangun kesan atau branding di mata publik. Strategi ini dilakukan Humas Untar dengan menggunakan enam konsep personal branding, yaitu spesialisasi, kepribadian, perbedaan, kenampakan, kesatuan, dan keteguhan. Guna membangun reputasi yang jujur dan kredibel terhadap publik, Humas Untar menggunakan mahasiswa asli dan aktif sebagai talent dalam TikTok @untarjakarta.